Application of change management methods in the transition process of Hungarian agricultural enterprises - Juhász, Gábor; Máthé, A.; Mach, T. (Acta Agraria Kaposváriensis, 1999)
The socio-economic transition in Hungary has made agricultural enterprises change their organisation pattern to enable them to incorporate themselves into the new context of the market economy, particularly when the idea of joining the EU bThe socio-economic transition in Hungary has made agricultural enterprises change their organisation pattern to enable them to incorporate themselves into the new context of the market economy, particularly when the idea of joining the EU becomes more a fact than simple speculation. Alterations in the inner and outer environment have forced such enterprises to change their organisational structure and behaviour patterns; however, the changes required do not occur spontaneously, so it is a prerequisite that organisational development methods and experts be involved. The system of changes induces a complex web of multilevel and multidirectional sets of modifications – all pushing the enterprises towards a turning point at which they can become real beneficiaries of the changes. Organisation development – a process and a method – may also present a possibility for the agricultural enterprises to turn their handling of actual changes into a process within which they can develop both their organisational and their human structure in a manner as desired.ecomes more a fact than simple speculation. Alterations in the inner and outer environment have forced such enterprises to change their organisational structure and behaviour patterns; however, the changes required do not occur spontaneously, so it is a prerequisite that organisational development methods and experts be involved. The system of changes induces a complex web of multilevel and multidirectional sets of modifications - all pushing the enterprises towards a turning point at which they can become real beneficiaries of the changes. Organisation development - a process and a method - may also present a possibility for the agricultural enterprises to turn their handling of actual changes into a process within which they can develop both their organisational and their human structure in a manner as desired.
Keywords: organisation development OD; organisational behaviour